If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -9x = 54 + -23x Solving 14 + -9x = 54 + -23x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23x' to each side of the equation. 14 + -9x + 23x = 54 + -23x + 23x Combine like terms: -9x + 23x = 14x 14 + 14x = 54 + -23x + 23x Combine like terms: -23x + 23x = 0 14 + 14x = 54 + 0 14 + 14x = 54 Add '-14' to each side of the equation. 14 + -14 + 14x = 54 + -14 Combine like terms: 14 + -14 = 0 0 + 14x = 54 + -14 14x = 54 + -14 Combine like terms: 54 + -14 = 40 14x = 40 Divide each side by '14'. x = 2.857142857 Simplifying x = 2.857142857
| 2*(x+4)-16=98+x | | K-7=-42 | | 16+2x=2x-16 | | -7/9+1/7=N | | y=-.50(-2.75+.25y)+2 | | x-8=3x+4 | | 17/7=2X-3X | | 5x+7.5y=3500 | | 76-4x=68-2x | | (n^2)-8n+12=0 | | 3x+96=8x-9 | | (r^2)-12r+27=0 | | (4x^(1/3))*(x^(1/2)) | | 37-3x=15x+15 | | p+14=28 | | -2v-v+12=-3v^2+6 | | 2x/3x-8 | | 2x-4=2x | | C/-3=0.3 | | 10x+9x=23 | | 6000-5x/5x=1/4 | | m/3+11=29 | | x^2+16x-100=0 | | 14x+7=22 | | 4x-.5x+2=-11 | | 6[4(2x-3)-3(4x-6)]=2x-16 | | pq=3p-2q | | 4x+-.50x+2=-11 | | 32-6x=3x+19 | | 4[4(5x-1)-2(3x-7)]=2x-122 | | 105+22+C=180 | | 24+3x=x-12 |